A Study to Assess the Effectiveness of Child to Child Approach on Knowledge and Practices Regarding Hand Washing among the Primary School Children of a Selected School Faridkot, Punjab (International Journal of Nursing Education, 2019)
Introduction: Hand washing is part of our life. Hands are the main cause for disease transmission. They spread vector infection from one person to another. Hand washing with soap (HWWS) is a simple and effective measure to prevent transmission of fecaloral disease and other infectious diseases in school-age children. There are over 10 million episodes of food related infection in a year but most of these are probably related to improper hand washing. Many of these deaths are easily preventable through simple practices such as hand washing with soap. Evidence suggests that improved hand washing can have a major impact on public health in any country and significantly reduce the two leading causes of childhood mortality. There is need to enhance the knowledge and practice skill of hand washing among school children. Aim of the Study: Aim is to assess the effectiveness of child to child approach on knowledge and practices regarding hand washing among the primary school children of a selected school of Faridkot, Punjab. Material and Method: A quantitative approach with one group pre test-post test research design was selected for the present study. With simple random sampling (100) school children from the 3rd,4th and 5th classes, selected the 10 students from the all study subjects. Then pre test of whole children were taken. After pre test, intervention was given to the selected 10 students about hand washing after that, post test was taken, and allowed the selected students to teach the other students about hand washing. Socio demographic data sheet and tool, structured knowledge interview performa and observational checklist were prepared to assess the effectiveness of child to child approach on knowledge and practices regarding hand washing. Results: The present study revealed that interventions i.e. child to child approach were helpful in improving hand washing knowledge and practices among primary school children, post test mean score of knowledge was 15.2 respectively which was significant at p value <0.05, similarly post test mean of hand washing practices was 10.41, which was significant at p <0.05 level. Conclusion: Child to child approach is an effective intervention to raise the level of knowledge and improve the practices of hand washing. After being instructed, primary school children taught each other and to their siblings, playmate, and friends at home. There is no or little need of any supervision.